Idosos hipertensos: acesso e utilização dos serviços de saúde - Deus, Kátia Maria Marques Sousa de (2015)
The aging of the population, comes with goals, different responsibilities and challenges to be met by global authorities Elderly population monitoring is characterized by great vulnerability, and so the demand for health services grows significantly. They have high rates of chronic and disabling diseases; among them we highlight the systemic hypertension (SH), as it constitutes one of the most prevalent health problems today and major risk factor for cardiovascular disease. Access to health services becomes crucial for ensuring prevention, rehabilitation and healing, especially in rural areas, due to a lower supply of health services. This research aimed to study the access and utilization of health services by elderly hypertensive patients registered at FHS UBS Vila Maranhão. The study is characterized as descriptive, exploratory quantitative approach. Was held in Vila Maranhão countryside of São Luís near the elderly enrolled in the FHS Health Center Yves Parga, UBS site. Counted with a sample representation of 164 elderly registered. For data collection we used a form with 29 semi structured questions. The collected data were organized and analyzed in Microsoft Excel 2013 program and analyzed in BioEstat software - Version 5.3. The results demonstrate the socioeconomic and demographic research that most elderly hypertensive patients is between 70 and 74anos, are female, of brown color, with elementary school, married, Catholic, living with children and grandchildren, have their own and masonry house and are retired; have a family income of two minimum wages, without health insurance and have comorbidities. In lifestyle checks that do not smoke, ingest alcoholic beverages and do not exercise. In the investigation of access and utilization of health services results show that receive visit 1time / month FHS in the person of ACS and very few vaccinate and consult at home; UBS seek for medical attention receive medication, vaccination and spontaneous measurement of PA. Use buses to transport and take about 20 minutes to get to the Unit, say they are satisfied with the service despite citing difficulties such as medical absenteeism, delay and disruption in service, high demand, lack of medicine. Seek other US for care. The evaluation of the supply and use of health services by the elderly can measure the effectiveness of health policies and verify the need for a reformulation of care and reorganization of services in order to facilitate the access and accommodating appropriate way. In Vila Maranhão, strategies need to be created and efforts for the implementation of actions and rationalization of resources in order to minimize the difficulties that prevent to meet in full and equal the old tracking